The labor market in New Zealand, 2000-2021 - David C. Maré (IZA World of Labor, 2022)
New Zealand is a small open economy, with large international labor flows and skilled immigrants. After the global financial crisis (GFC) employment took four years to recover, while unemployment took more than a decade to return to pre-crisis levels. Maori, Pasifika, and young workers were worst affected. The Covid-19 pandemic saw employment decline and unemployment rise but this was reversed within a few quarters. However, the long-term impact of the pandemic remains uncertain.
Keywords: J01; R00; 330; New Zealand; immigration; wages; unemployment; wage compression; GFC; Covid-19